Use of Medication Error Simulations in Continuing Professional Education to Effect Change To Practice - Jeanne Frenzel; Heidi Eukel; Rebecca Brynjulson (University of Minnesota Libraries Publishing, 2020)
Introduction: A novel continuing professional education CPE training program and simulation were used to teach pharmacists and pharmacy technicians about continuous quality improvement and how to identify, report, and communicate information regarding medication related errors using root cause analysis.   Methods: Pharmacists and pharmacy technicians attending a statewide pharmacy association meeting voluntary attended a CPE training program and simulation.  During the simulation, learners investigated and identified medication related errors in three different pharmacy settings.  A collection of items found at each pharmacy and audio recordings were used by learners to identify the medication related error.  After each simulation, facilitators led a debriefing to discuss the learners' experiences.  Data was collected using online surveys.  Descriptive statistics and chi-square tests were used to analyze the data. Results:  Fourteen months following the program, 15 of the 67 participants responded to an anonymous survey.  Of the 15 responding participants, 73.3% (11/15) were confident or very confident they could establish or maintain a high-quality continuous quality improvement plan at their practice site.  Sixty percent (9/15) felt the experience reinforced their current practices, 13.3% (2/15) had implemented changes to their practice, and 13.3% (2/15) felt they needed more information before considering changes to their practice.  Reported barriers to establishing a continuous quality improvement program were time constraints, 40.0% (6/15), system constraints, 26.7% (4/15), or lack of staff 20.0% (3/15). Conclusion: A CPE training program and simulation reinforced practice for pharmacy personnel, resulted in changes to practice, and positively increased participants' confidence in establishing a continuous quality improvement plan in the workplace.